Prospective clinical performance of CoVarScan in identifying SARS-CoV-2 Omicron subvariants - Kenneth Zhu; Manoj Sah; Lenin Mahimainathan; Yan Liu; Chao Xing; Karen Roush; Andrew Clark; Jeffrey SoRelle (Microbiology Spectrum)
ABSTRACT The purpose of this work was to evaluate the performance of CoVarScan, a multiplex fragment analysis approach, in identifying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of the Omicron lineage rapidly and accurately. The ability to identify variants with high fidelity and low turnaround time is important both epidemiologically and clinically for pandemic monitoring and therapeutic monoclonal antibody (mAb) selection. Currently, the gold-standard test for this task is whole-genome sequencing (WGS), which is prohibitively expensive and/or inaccessible due to equipment requirements for many laboratories. Omicron variants have been closely related, so the ability of genotyping tests to differentiate them is an important, outstanding question. CoVarScan uses PCR targeting eight SARS-CoV-2 mutational hot spots. In total, 4,918 SARS-CoV-2-positive cases between 17 December 2021 and 31 January 2024 were included in the analysis. CoVarScan achieved 96.5% concordance with WGS and could detect unique mutational signatures for BA.1, BA.2, BA.2.12.1, BA.4/BA.5, BA.2.75, XBB, and BA.2.86. These are the major variants of concern (VOCs) that have dominated since Omicron originally appeared in December 2021. Lastly, based on panel design, we predict a unique mutational pattern for the newly emergent, highly mutated variant BA.2.87. CoVarScan can rapidly, accurately, and cost-effectively identify all Omicron variants in a scalable manner. Furthermore, CoVarScan does not require design alterations to detect new VOCs. CoVarScan performs as accurately as WGS with higher sensitivity, allowing its use as a tool to quickly identify variants for epidemiological surveillance and clinical decision-making in the selection of effective therapeutic mAbs.IMPORTANCEAlmost 5 years since the start of the pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern continue to emerge, with mutations conferring new properties like increased transmissibility and resistance to therapeutic monoclonal antibodies and vaccines. Conventionally, whole-genome sequencing (WGS) has characterized new SARS-CoV-2 variants, but results come too late for clinical actionability. WGS suffers from high failure rates for samples with low viral RNA and is inaccessible for lower-resource laboratories. As new variants like Omicron appear, it is necessary to develop rapid and accurate testing to distinguish between variants. Fast and accurate identification of sensitive viral lineages would allow tailored use of monoclonal antibodies that may otherwise have been pulled from the market due to rising overall resistance. Rapid results also allow public health officials to make policy decisions in time to reduce morbidity and mortality for sensitive populations such as patients who are immunocompromised or have significant medical comorbidities.